2012
DOI: 10.3109/13697137.2012.688078
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of women with menopausal hot flushes and night sweats

Abstract: This sample of relatively healthy mid-aged women with vasomotor symptoms reported reduced HrQoL compared to age-matched norms and a general sample of menopausal women. Problem rating, rather than frequency, of hot flushes was associated with reduced HrQoL, as were health and psychosocial factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 19 publications
2
60
0
2
Order By: Relevance
“…2 Hot flashes consistently have been shown to be associated with discomfort, sleep disturbances, fatigue, and decreased quality of life. 3 In addition, a recent study showed that, because of the negative effects of hot flashes on women's lives, women with hot flashes have lower work productivity and greater healthcare resource use than women without hot flashes. 4 There is also some indication that hot flashes are associated with an increased risk of more serious adverse health outcomes, including cardiovascular disease 5 and depression.…”
Section: Introductionmentioning
confidence: 99%
“…2 Hot flashes consistently have been shown to be associated with discomfort, sleep disturbances, fatigue, and decreased quality of life. 3 In addition, a recent study showed that, because of the negative effects of hot flashes on women's lives, women with hot flashes have lower work productivity and greater healthcare resource use than women without hot flashes. 4 There is also some indication that hot flashes are associated with an increased risk of more serious adverse health outcomes, including cardiovascular disease 5 and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Vasomotor symptoms (VMS) associated with menopause, such as hot flashes and night sweats, affect up to 80% of menopausal women,1 negatively impact quality of life and daily functioning,2 and cause many women to seek treatment 3. Although hormone therapy is approved for the treatment of moderate to severe VMS associated with menopause,4 safe and effective nonhormonal alternatives to hormone therapy are needed.…”
mentioning
confidence: 99%
“…Problem rating-i.e., the extent to which symptoms are bothersome and interfere with life-was chosen, before the trial began, as the primary outcome because problem rating, rather than frequency, is associated with quality of life [4], and it has been recommended as an appropriate patient reported outcome measure in clinical trials of HFNS treatments [32,33]. The scale has good internal consistency (Cronbach α=0.9) and test-retest reliability (r=0.8) [5].…”
Section: Self-help Cbt Intervention (Sh-cbt)mentioning
confidence: 99%
“…Hot flushes and night sweats (HFNS) are the main symptoms of the menopause, which for an estimated 20-25% affect quality of life (QOL) largely due to discomfort, embarrassment and the impact of night sweats upon sleep [3,4].…”
Section: Introductionmentioning
confidence: 99%